Living Fossil : The Story of the Coelacanth - Thomson, Keith Stewart (New York W. W. Norton & Company, 1991)
Tells the strory of a fish, the coelacauth, thought extinct for 70 million years, which was discorered in 1938 in the Indian Ocean.
Include Pictures, Maps, Notes and Index
Keywords: Coelacanth -- Fishes